Apa yang Dipikirkan Orang Tua: Perspektif Kesiapan Sekolah - Hapidin Hapidin; Yuli Pujianti; Nurbiana Dhieni (Pendidikan Guru PAUD Universitas PGRI Semarang, 2024)
Abstract School readiness is an essential factor for the academic success of primary school students, and children's social skills influence it, as well as teachers' understanding of transitional learning and parental support. This study examines students' school readiness, focusing on these three variables. Through a survey using tests, questionnaires, interviews and document analysis, this study was conducted among elementary school students in DKI Jakarta. It also developed a standardized school readiness instrument and a transition learning model for early-grade teachers. Results show that 50% of parents prioritize reading, 48.8% writing and 38.1% arithmetic as academic readiness. However, non-academic aspects such as disciplinary behaviour (98.8%), social skills (98.8%), emotion regulation (98.9%), independence (98.9%), and self-confidence (100%) were highly prioritized. In addition, 100% of parents supported a conducive educational atmosphere, teachers who respect students, a playful approach in the early grades, and fun learning media. In conclusion, school readiness covers academic and non-academic aspects in a balanced way, contributing to national policies to support developmentally appropriate transition learning in the early grades of primary school. The findings support Government policy in developing developmentally appropriate transition learning models for young children in the early grades of primary school. Keywords: School Readiness; Transitional Learning Model; Literacy Numeracy; Social Skills Abstrak Kesiapan sekolah merupakan faktor penting bagi keberhasilan akademis siswa sekolah dasar, dipengaruhi oleh keterampilan sosial anak, pemahaman guru tentang pembelajaran transisi, dan dukungan orang tua. Penelitian ini bertujuan menguji kesiapan siswa masuk sekolah, dengan fokus pada ketiga variabel tersebut. Melalui survei menggunakan tes, kuesioner, wawancara, dan analisis dokumen, penelitian ini dilakukan pada siswa sekolah dasar di DKI Jakarta. Penelitian ini juga mengembangkan instrumen standar kesiapan sekolah dan model pembelajaran transisi bagi guru kelas awal. Hasil menunjukkan bahwa 50% orang tua memprioritaskan kemampuan membaca, 48,8% menulis, dan 38,1% berhitung sebagai kesiapan akademik. Namun, aspek non-akademik seperti perilaku disiplin (98,8%), keterampilan sosial (98,8%), regulasi emosi (98,9%), kemandirian (98,9%), dan kepercayaan diri (100%) sangat diprioritaskan. Selain itu, 100% orang tua mendukung suasana pendidikan kondusif, guru yang menghargai siswa, pendekatan bermain di kelas awal, dan penggunaan media pembelajaran yang menyenangkan. Kesimpulannya, kesiapan sekolah mencakup aspek akademik dan non-akademik secara seimbang, berkontribusi pada kebijakan nasional untuk mendukung pembelajaran transisi yang sesuai dengan perkembangan anak usia dini di kelas awal sekolah dasar. Temuan ini mendukung kebijakan pemerintah dalam mengembangkan model pembelajaran transisi yang sesuai dengan perkembangan anak usia dini di kelas awal sekolah dasar. Kata kunci: Kesiapan Sekolah; Model Pembelajaran Transisi; Literasi Numerasi; Keterampilan Sosial